prove that

Asked by  | 6th Jun, 2008, 07:25: PM

Expert Answer:

(cos3A+sin3A )/( cosA+ sinA)+(cos3A-sin3A) / (cosA-sinA)

= [(cosA+sinA)(cos2A+sin2A-cosAsinA)] / ( cosA+ sinA)   +  [(cosA-sinA)(cos2A+sin2A+cosAsinA)] / ( cosA- sinA)

= (cos2A+sin2A-cosAsinA) + (cos2A+sin2A+cosAsinA)]

= cos2A+sin2A-cosAsinA + cos2A+sin2A+cosAsinA

= 1 -cosAsinA + 1 + cosAsinA

= 2

Answered by  | 7th Jun, 2008, 08:09: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.